2002
DOI: 10.1177/1362361302006003005
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Parent Management Training to Increase Self-Efficacy in Parents of Children with Asperger Syndrome

Abstract: This study was a trial of an intervention programme aimed to improve parental self-efficacy in the management of problem behaviours associated with Asperger syndrome. The intervention was compared across two formats, a 1 day workshop and six individual sessions, and also with a non-intervention control group. The results indicated that, compared with the control group, parents in both intervention groups reported fewer problem behaviours and increased self-efficacy following the interventions, at both 4 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
0
10

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(162 citation statements)
references
References 21 publications
9
143
0
10
Order By: Relevance
“…Changes made during the intervention could very well improve the home environment post-treatment, making this setting more conducive to social gatherings, decreasing family disruption that often impedes social opportunities, and helping eliminate conflict that exacerbates ASD symptomology (Kelly et al 2008). In addition, the fact that parenting self-efficacy showed a statistically significant increase following PEERS intervention (though this was not significant over and above the waitlist control group) appears very important given the relationship between parenting selfefficacy and child behavior problems (Sofronoff and Farbotko 2002). and permission has been granted for this version to appear in e-Publications@Marquette.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes made during the intervention could very well improve the home environment post-treatment, making this setting more conducive to social gatherings, decreasing family disruption that often impedes social opportunities, and helping eliminate conflict that exacerbates ASD symptomology (Kelly et al 2008). In addition, the fact that parenting self-efficacy showed a statistically significant increase following PEERS intervention (though this was not significant over and above the waitlist control group) appears very important given the relationship between parenting selfefficacy and child behavior problems (Sofronoff and Farbotko 2002). and permission has been granted for this version to appear in e-Publications@Marquette.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in parenting self-efficacy (PSE) is important to assess given the association between low PSE and increased levels of parenting stress in parents of children with disabilities (Giallo et al 2011). Sofronoff and Farbotko (2002) noted that increased PSE postintervention was associated with fewer reported child behavior problems, suggesting that increases in PSE provides a direct benefit to the child with ASD.…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Considerando que a promoção do sentimento de competência parental tem sido um dos focos mais salientes dos programas de formação/educação parental (e.g., Peterson, Tremblay, Ewigman, & Saldana, 2003;Sofronoff & Farbotko, 2002), é fundamental compreender as associações entre as percepções de auto-eficácia parentais de domínio geral e específico, quer para as mães, quer para os pais. Neste sentido, o presente estudo constitui-se como um contributo para este inquérito.…”
Section: Domínio Específico E Domínio Geral Da Auto Eficácia Percebidaunclassified
“…Moreover, most of these studies are limited in inferences of directionality due to their cross-sectional design. The predictive power of self-efficacy has nonetheless been partially demonstrated in studies where interventions aimed at fostering PSE have been found to decrease child behavior problems (e.g., Sofronoff & Farbotko, 2002). Among studies on PSE, several have explored its relation with parenting, whereas others have investigated its direct associations with child outcomes.…”
Section: Parental Behavior and Epb Trajectoriesmentioning
confidence: 99%